Surface Conditions Analysis of Polymeric Insulators Under Contamination Effects - Rozi, N. M.; Othman, N. A.; Adzis, Z.; Kamarden, H.; Rahman, R. A.; Baharom, M. N. R.; Kamarudin, M. S. (International Journal of Integrated Engineering, 2020)
A good polymer insulator can maintain the hydrophobic surface properties. However, polymer insulator is exposed to the environment which may lead to the deposition of rain water or factory oil. Oil is categorized as hydrophobic while water has a hydrophilic feature which when deposit on the insulator surface, it may affect the performance of insulator. Therefroe, this paper studies the effect of water and oil contamination on current density and space charge distribution along 15 kV polymeric insulators particularly ethylene propylene-diene monomer (EPDM) and silicone rubber (SiR). A three-dimensional model of polymeric insulator was designed using a finite element software to evaluate the current density and space charge distribution while the experimental works was conducted in the laboratory to measure the charge distribution only. The results reveal that both current density and charge distribution is affected depend on the conductivity of contamination conditions. Both results extracted from simulation and experimental is in agreement where the EPDM insulator have higher amplitude of charge compared to SiR insulator.